1030 nm All-Fiber Closed-Loop Fiber Optic Gyroscope with High Sensitivity. (6th October 2022) - Keskin, Hakan; Vural, Hüseyin Avni; Altınöz, Bağış; Bektik, Ümit; Altan, Hakan
Abstract : Angle random walk (ARW) is a critical noise component of a typical gyroscope alongside with bias instability noise. ARW has dominant effects especially in short-term accuracy. The measurement uncertainty degrades with the deterioration in ARW resulting in the lowered overall gyroscope accuracy. Many inertial navigation applications such as satellite control and gyro-compassing require low ARW. For an interferometric fiber optic gyroscope, lowest detectable rotation is proportional to scale factor of sensor and inversely proportional to optical bandwidth of light source used in the gyroscope. In this study, using a novel pump laser control closed-loop method, gyroscope performance is able to significantly enhance including signal-to-noise ratio (SNR). Fiber optic gyroscope includes an Yb-doped amplified spontaneous emission (ASE) source with broad emission spectra of 15 nm bandwidth used as light source in order to improve gyroscope sensitivity. The final ARW performance is about 0.008°/√hr for a fiber coil of 150 m length.